(untitled) (Global Journal of Science Frontier Research, 2019)
In developing countries, such as, Ethiopia, rainfall is the crucial factor for determining Gross domestic product (GDP). In this study, different types of statistical analysis were performed to understand the reasons behind the rainfall variability from monthly to inter decadal levels during 1981 to 2017. With the exception to rainfall from December to March, although not statistically significant, increasing trends have been noticed during most of months. During the El Niño, a greater reduction in the summer season’s rainfall Kiremt (June to September) noticed, whereas, enhancement during the end of winter to spring season Belg (February to May) observed. In contrast, during La Nina an increasing trend observed for the Kiremt, but decreasing trend observed for both Belg and Bega (October to January). Most of these changes indicate the role of Tropical Pacific Ocean’s sea surface temperature (SST) coupled with atmospheric circulation regulating principally the rainfall of the study area.